Europe's Crisis: Market competition instead of social bonds - WICKHAM, JAMES (Tasc, 2013)
Europe's crisis is not just an economic crisis, but a crisis of social inclusion and social cohesion. This is in turn the result of the failure of the European Union to live up to the promise of the European Social Model
PUBLISHED
Dublin
Keywords: Europe; social cohesion; social inclusion; European Social Model; Inclusive Society; International Integration